Ultrasonic studies of \(Ni(NO_3)_{2}.6H_{2}O\) in glycol + water solvent at 303.15 K - Patnaik, Ajaya; Mishra, Sashibhusan (International Journal of Advanced Chemistry, 2014)
Various acoustic parameters such as isentropic compressibility \((β_s)\), intermolecular free length (Lf), apparent molar volume \((Φ_v)\), apparent molar compressibility \((Φ_k)\), molar compressibility (W), molar sound velocity (R), acoustic impedance (Z) of Ni(NO3).6H2O in 10%, 20% and 30% Glycol + Water at 303.15K have been determined from ultrasonic velocity (U), density (p) and relative viscosity \((η_r)\) of the solution. These parameters are related with the molar concentration of the solution and reflect the distortion of the structure of the solvent i.e. Glycol + Water.Keywords: Ultrasonic Velocity, Acoustic Parameter, Density, Relative Viscosity, Glycol + Water.